Dependency theory re-visited : the case of Latin America - Ökten, Nilay (My University, 2020)
ÖZBAĞIMLILIK KURAMI: LATİN AMERİKA ÖRNEĞİÖKTEN, NİLAYYüksek Lisans, Siyaset Bilimi Ve Uluslararasi İlişkiler Anabilim DaliTez Danışmanı: Dr. Emrehan Zeybekoğlu2020Bu tezde Bağımlılık kuramı ve Latin Amerika politik ekonomisi incelenmiştir. Bağımlılık kuramı çerçevesinde Latin Amerika’nın dünya ekonomik sistemindeki yeri araştırılmış ve Bağımlılık teorisinin kıtanın politik ekonomisini analiz etmekte geçerliliğini koruduğu sonucuna varılmıştır. Nitel ve nicel verilerle desteklenen bu inceleme teorinin argümanlarına dayanarak Latin Amerika’nın ekonomi politiğini analiz etmiştir. TABLE OF CONTENTSPage NumberÖZiABSTRACTiiLIST OF TABLESvLIST OF FIGURESviABBREVIATIONSvii1.INTRODUCTION22.DEPENDENCY THEORY112.1.Theoretical Background112.2.Dependency Theory in Latin America242.3.New Dependence383.DEVELOPMENT AND GLOBALIZATION463.1.Theoretical Framework of Development463.2.Theoretical Background of Globalization523.3.The History of Globalization553.4.Globalization in Latin America714.DEPENDENCY THEORY: THE CASE OF LATIN AMERICA904.1.Post-Neoliberalism944.2.Economic Policies Implemented in Latin America984.3.Summary of the Economic Paradigm of Latin America Throughout Its History1225.CONCLUSION130BIBLIOGRAPHY147

This thesis focuses on Dependency Theory in the context of Latin America. Within the framework of Dependency theory, the place of Latin America in the world economic system has been researched and it has been concluded that Dependency theory remains valid in analyzing the political economy of the continent. This work, supported by qualitative and quantitative data, analyzed the political economy of Latin America based on the arguments of the theory.TABLE OF CONTENTSPage NumberÖZiABSTRACTiiLIST OF TABLESvLIST OF FIGURESviABBREVIATIONSvii1.INTRODUCTION22.DEPENDENCY THEORY112.1.Theoretical Background112.2.Dependency Theory in Latin America242.3.New Dependence383.DEVELOPMENT AND GLOBALIZATION463.1.Theoretical Framework of Development463.2.Theoretical Background of Globalization523.3.The History of Globalization553.4.Globalization in Latin America714.DEPENDENCY THEORY: THE CASE OF LATIN AMERICA904.1.Post-Neoliberalism944.2.Economic Policies Implemented in Latin America984.3.Summary of the Economic Paradigm of Latin America Throughout Its History1225.CONCLUSION130BIBLIOGRAPHY147
Keywords: Bağımlılık kuramı; Capitalist World Economy; Dünya-Sistemleri analizi; International relations; Kapitalist Dünya Ekonomisi Dependency theory; Latin America; Latin Amerika; Political science; Siyasal bilim; Uluslararası ilişkiler; World-Systems analysis